Ethno-Science Study of Bamboo as A Building Material of Baduy Community for Environmentally Friendly and Sustainable Materials Chemistry Learning - Widyaningsih, Mia; Sriyati, Siti; Liliawati, Winny; Mudzakir, Ahmad (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2024)
This study aims to develop the chemical aspects of the local practice of the Baduy community in utilizing bamboo as a traditional house building material that can be integrated in material chemistry learning. The research method is a literature study of scientific journals, books, online articles, and research reports related to bamboo as a building material, which is then analyzed by comparing local knowledge and scientific concepts to identify potential integration into science learning, especially chemistry. The result of this study is that the integration of natural science with local practices, such as bamboo used for environmentally friendly and sustainable building materials, is an innovative way to teach materials chemistry. The study of bamboo as a building material can help students understand chemistry concepts, especially the structure and physicochemical properties of materials so that students can relate the mechanical and thermal characteristics of materials to their structure in a more relevant and practical way. Thus, chemistry learning is not only limited to theory and laboratory experiments, but also includes real applications that are relevant to everyday life in society.